The Inhibition of Glutathione S-Transferases and Butyrylcholinesterase by Antidepressants: A Mini-Review on Enzyme-Drug Interactions - Markus, Victor; Dalmızrak, Özlem; Teralı, Kerem; Özer, Nazmi (Current Enzyme Inhibition, 2022)
Background: Compromises in the cellular enzymatic defense barrier can increase the duration of exposure to electrophiles and the severity of toxicity they may incur. Objective: In this mini-review, we discuss the inhibition of the enzymatic defense systems by different antidepressants commonly prescribed worldwide as well as herbal products used for various forms of depression. Methods: Our work primarily focused on the interactions of two prominent biotransformation enzyme systems, namely glutathione S-transferases and cholinesterases, with tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs), and hypericin. Results: The antidepressants exert considerable inhibitory effects against glutathione -transferases and butyrylcholinesterase. Conclusion: The outcomes of available published studies and their implications for health and disease are discussed here in detail.
Keywords: tricyclic antidepressants